Concussion Management Plans' Compliance with NCAA Requirements: Preliminary Evidence Suggesting Possible Improvement. Issue 2 (June 2017) - Baugh, Christine M.; Kroshus, Emily; Perry, Kaitlyn I.; Bourlas, Alexandra P.
This study examined the extent to which concussion management plans at National Collegiate Athletic Association (NCAA) member schools were in line with NCAA Concussion Policy and best practice recommendations in absence of any process to ensure compliance. Most schools' concussion management plans were in compliance with 3 (60%) or 4 (25.6%) of the NCAA's 4 required components. Annual athlete education and acknowledgement was the requirement least often included, representing an area for improvement. Further, schools tended to more often include best practices that were more medically-oriented (e.g., including baseline examination), compared to best practices that were less medical in nature (e.g., avoiding flagrant head hits).